Association of thyroid autoimmunity with the presence and severity of coronary atherosclerosis in patients undergoing coronary angiography. Issue 39 (30th September 2022) - Yang, Libo; Zhang, Mingliang; Zhang, Hui; Zheng, Guanlin; Xu, Chao; Li, Guangyao
Abstract : Studies on the association of thyroid autoimmunity with cardiometabolic risk and coronary artery disease (CAD) have produced conflicting results. This study aimed to investigate the relationship of thyroid autoimmune bodies (thyroid peroxidase antibody [TPOAb] and thyroglobulin antibody [TgAb]) with CAD in euthyroid subjects undergoing coronary angiography. A total of 307 subjects who underwent coronary angiography were included. The severity of coronary atherosclerosis was evaluated by using Gensini score. Serum TSH, total T3, total T4, TPOAb, TgAb, lipid levels et al were measured and compared between the groups with and without CAD. Logistic multivariate regression analysis were performed to assess the associations. Levels of thyroid hormones were comparable between the two groups. The positive percentage of anti-Tg antibodies was higher in non-CAD group (15.22% vs 7.91%, χ 2 = 3.95, p = .047) while no significant difference was observed for anti-TPO antibodies (19.57% vs 17.21%, χ 2 = 0.243, p = .622). The natural log-transformed Gensini score (ln (Gensini score)) was lower in the TgAb+ group (2.94 ± 1.11 vs 2.41 ± 1.18, P = .015). There was no significant difference for ln (Gensini score) between TPOAb− and TPOAb+ group (2.90 ± 1.14 vs 2.85 ± 1.09, P = .782). Logistical regression analysis revealed that positive TgAb was inversely associated with the presence of CAD (OR: 0.387, 95% CI: 0.157–0.952, p = .039) independent of other risk factors. The results showed that TgAb positivity might be an independent protective factor for CAD.